Transcriptome analysis suggests a role for the differential expression of cerebral aquaporins and the MAPK signalling pathway in human temporal lobe epilepsy. (21st August 2017) - Salman, Mootaz M.; Sheilabi, Mariam A.; Bhattacharyya, Dev; Kitchen, Philip; Conner, Alex C.; Bill, Roslyn M.; Woodroofe, M. Nicola; Conner, Matthew T.; Princivalle, Alessandra P.
Abstract: Epilepsies are common disorders of the central nervous system (CNS), affecting up to 2% of the global population. Pharmaco‐resistance is a major clinical challenge affecting about 30% of temporal lobe epilepsy (TLE) patients. Water homeostasis has been shown crucial for regulation of neuronal excitability. The control of water movement is achieved through a family of small integral membrane channel proteins called aquaporins (AQPs). Despite the fact that changes in water homeostasis occur in sclerotic hippocampi of people with TLE, the expression of AQPs in the epileptic brain is not fully characterised. This study uses microarray and ELISA methods to analyse the mRNA and protein expression of the human cerebral AQPs in sclerotic hippocampi (TLE‐HS) and adjacent neocortex tissue (TLE‐NC) of TLE patients. The expression of AQP1 and AQP4 transcripts was significantly increased, while that of the AQP9 transcript was significantly reduced in TLE‐HS compared to TLE‐NC. AQP4 protein expression was also increased while expression of AQP1 protein remained unchanged, and AQP9 was undetected. Microarray data analysis identified 3333 differentially regulated genes and suggested the involvement of the MAPK signalling pathway in TLE pathogenesis. Proteome array data validated the translational profile for 26 genes and within the MAPK pathway (e.g. p38, JNK) that were identified as differentially expressed from microarray analysis. ELISA data showed that p38 and JNK inhibitors decrease AQP4 protein levels in cultured human primary cortical astrocytes. Elucidating the mechanism of selective regulation of different AQPs and associated regulatory proteins may provide a new therapeutic approach to epilepsy treatment. Abstract : Transcriptome data indicates significant upregulation of AQP1 and AQP4 transcripts; with a significant downregulation of AQP9 transcript in TLE‐HS compared to TLE‐NC. The expression of AQP4 protein was increased, while AQP1 protein remained unchanged, and AQP9 was undetected. Proteome profiling validated the translational profile for 26 genes within the MAPK pathway. ELISA data showed that inhibiting p38 or JNK decreases AQP4 protein levels in cultured human primary cortical astrocytes.